Options in foreign economic relations for Central and Eastern Europe - Michael Dauderstädt (Intereconomics, 1994)
Following the collapse of the CMEA, the foreign trade of the countries of Central and Eastern Europe declined drastically with dire consequences for output, incomes and employment in these countries. What options do the former CMEA members have for revitalizing their foreign trade? What impediments will have to be surmounted in each case?
Keywords: 330; System Transformation